A microcontroller implementation of harmonic control arrays method [Harmonik Denetim Dizileri Yönteminin Bir Mikrodenetleyici Uygulamasi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
Harmonic Control Arrays (HCA) is a method based on adjusting the harmonic components of the control signal to minimize the error signal for systems with periodic references and disturbances. In this study the results of a discrete-time implementation of HCA with a microcontroller as the control unit has been represented. A low-pass filter (LPF) and a nonlinear electronic circuit has chosen as the plant, and a periodic sinusoidal reference signal have been applied on it. © 2017 IEEE.
Keywords: discrete time control; nonlinear signal processing; signal processing hardware